Integrasi Nilai Kepemimpinan Islami dalam Pendidikan Modern: Kajian Literatur dan Perspektif Al-Qur’an - M Nor Kholis; Muhammad Husni (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the integration of Islamic leadership values in modern education from the perspective of the Qur’an. The research employed a library research method with a descriptive qualitative approach. Data sources consisted of the Qur’an, Qur’anic commentaries (tafsir), Islamic leadership books, and various scholarly journals. The findings reveal that the values of trustworthiness (amanah), justice, consultation (shura), and responsibility are highly relevant in addressing the challenges of modern education. The implementation of these values can be carried out through a culture of discipline, effective school leadership, moral habituation, and the strengthening of Islamic character. The integration of Islamic leadership values contributes to the development of students who possess noble character, responsibility, and strong moral integrity.